The inclusion of collaborative processes in the contract to achieve high performance construction projects - Franco Regjo, Eric (2020)
In recent years, in Latin America, reference has been frequently made to “collaborative” contracts. However, there is no common understanding of what this term means and the relevant international discussion and development. This article seeks to establish the framework of the discussion on alternatives available to increase productivity in the construction industry and how this has led to seeing the contract as a useful tool to promote said process.